Migrated intrauterine contraceptive device: erosion in to sigmoid colon - Kumar, Hitesh; Sharma, Prashant; Aggarwal, Beena (International Journal of Research in Medical Sciences, 2018)
Intrauterine contraceptive devices (IUCDs) are one of the most widely chosen contraceptive methods with high efficacy, less side effects, and low cost especially in a developing country like India. Although they have low side effect profile but they are also associated with serious complications like device migration into adjacent organs, uterine perforation and sepsis. Any patient presenting with loss of thread should be assessed for localization of the IUCD. Authors are thereby reporting a case of a 30-year-old lady who presented with 2 month amenorrhea with loss of IUCD thread. She was diagnosed with intrauterine pregnancy with migrated IUCD into distal sigmoid colon. The patient was explored, IUCD was removed, dilatation and evacuation were done. Authors concluded that IUCDs are safe only in experienced hands and an institutional training is must for family planning workers. Patient education regarding regular checkup for threads is also emphasized.